A method for producing an oxide ceramic coating

CN117535758BActive Publication Date: 2026-10-27LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202311577977.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-24
Publication Date
2026-10-27
Estimated Expiration
2043-11-24

AI Technical Summary

Technical Problem

目前,在硅酸盐电解液体系中直接通过微弧氧化技术实现金属材料表面高含量的SiO2陶瓷涂层的制备仍未见有报道;申请号为202310236235.X的中国专利公开了一种基于微弧氧化制备的非晶二氧化硅涂层及其制备方法和应用,其是通过吸附有机硅化合物水解产生的凝胶,利用微弧氧化技术在6061铝合金表面实现了高含量非晶SiO2涂层的制备,但溶胶体系的稳定性及可控性相对较差,较难实现复杂结构件及零部件的大批量处理,同时也存在制备工艺适应范围较窄的缺陷,即该工艺只能在特定的基材表面得到SiO2涂层,而金属材料的表面化学活性和微弧氧化过程中的反应机制是不同的,这种差异会导致SiO2陶瓷涂层的制备工艺相对较复杂且具有唯一的特性,因而要在同种工艺条件下实现不同金属材料表面的相类似的SiO2陶瓷涂层的制备是十分困难的

Benefits of technology

[0019]本发明提供了一种氧化物陶瓷涂层的制备方法,包括以下步骤:将主成膜剂、成膜促进剂、辅助成膜剂和水混合,得到微弧氧化电解液;以基体为阳极,以不锈钢盘管为阴极,将所述阳极放置于所述微弧氧化电解液中,进行微弧氧化处理,得到所述氧化物陶瓷涂层。本发明所述制备方法具有普适性,即在不同的金属材料表面经由同一种工艺过程得到具有组分及性能相似的陶瓷涂层,极大地解决了微弧氧化技术应用过程中的工艺复杂性和可控性问题。本发明适用范围广,适用于各种型号及牌号的金属材料表面的非基体氧化物陶瓷涂层的制备,也适用于各种复杂结构的零部件表面。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117535758B_ABST
    Figure CN117535758B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of metal surface treatment, in particular to a preparation method of an oxide ceramic coating. The application provides a preparation method of an oxide ceramic coating, which comprises the following steps: mixing a main film forming agent, a film forming promoter, an auxiliary film forming agent and water to obtain a micro-arc oxidation electrolyte; taking a substrate as an anode and taking a stainless steel coil as a cathode; placing the anode in the micro-arc oxidation electrolyte to perform micro-arc oxidation treatment, so that the oxide ceramic coating is obtained. The preparation method has wide application range, good stability and good controllability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal surface treatment technology, and in particular to a method for preparing an oxide ceramic coating. Background Technology

[0002] Micro-arc oxidation (MAO) is a novel surface modification technology for valve metal materials (aluminum, magnesium, titanium, and their alloys). This technology utilizes the high voltage output from the MAO power supply to create a strong electric field at the solution / workpiece interface in an electrolytic cell. This causes the insulating film on the workpiece surface to break down, generating a micro-arc discharge, thereby growing a continuous and dense oxide ceramic coating in situ on the workpiece surface. By adjusting the combination of electrolyte and electrical parameters during the MAO process, similarly composed MAO ceramic coatings can also be prepared on the surfaces of non-valve metal materials (copper, iron, and their alloys).

[0003] Existing research reports suggest that micro-arc oxidation ceramic coatings are composed of composite oxides, with matrix oxidation as the main component and electrolyte compound adsorption-deposition-sintering as a secondary component. The main component of the oxide ceramic coating is the matrix oxide, which is relatively less affected by the composition of compounds in the electrolyte. For example, Chinese Patent Application No. 201810729654.6 discloses a method for preparing a conductive thermal control coating with low solar absorptivity and high emissivity on the surface of aluminum alloy. This method uses sodium silicate as the main film-forming agent and micro-arc oxidation technology to prepare a ceramic coating on the surface of aluminum alloy with aluminum oxide as the primary component. Chinese Patent Application No. 202110943294.1 discloses a method for preparing a self-supporting micro-arc oxidation film layer on magnesium alloy. This method prepares a magnesium oxide ceramic coating with low impurity content on the surface of different types of magnesium alloys, such as LA91 magnesium-lithium alloy and AZ31B magnesium alloy, in an electrolyte system with sodium silicate as the main salt. Chinese Patent Application No. 201310111042.8 discloses a method for preparing a coating with low solar absorptivity and high emissivity on the surface of titanium alloy. This method prepares a ceramic coating mainly composed of rutile titanium dioxide on the surface of titanium alloy in an electrolyte system with silicate as the main film-forming agent through micro-arc oxidation. In summary, micro-arc oxidation technology has difficulty in preparing ceramic coatings with non-matrix oxides as the main component on the surface of metal materials, which greatly limits the application of micro-arc oxidation ceramic coatings.

[0004] Silica ceramic coatings possess good thermal stability, chemical stability, excellent wear and corrosion resistance, and low absorption and high emission thermal control properties, making them a common ceramic coating material with wide applications in optics, electronics, material protection, and aerospace. Based on this, researchers have used methods such as vapor deposition, magnetron sputtering, and sol-gel to prepare SiO2 coatings on metal surfaces. However, the resulting SiO2 coatings suffer from problems such as thinness, poor adhesion to the metal substrate, complex processes, and high costs. SiO2 ceramic coatings obtained on metal surfaces through micro-arc oxidation technology are generally composite coatings. For example, Chinese patent application number 201911163435.7 discloses a method for preparing nano-ceramic coatings using chemical self-sintering micro-arc oxidation technology for ceramic particles. This method achieves the preparation of a highly wear-resistant 3Al2O3-2SiO2 composite ceramic layer on aluminum alloy surfaces by adding modified SiO2 ceramic particles to a base electrolyte. Currently, there are no reports on the preparation of high-content SiO2 ceramic coatings on metal surfaces directly through micro-arc oxidation technology in silicate electrolyte systems. Chinese patent application number 202310236235.X discloses an amorphous silica coating prepared based on micro-arc oxidation, its preparation method, and its application. It achieves the preparation of a high-content amorphous SiO2 coating on the surface of 6061 aluminum alloy by using micro-arc oxidation technology to generate a gel from the hydrolysis of adsorbed organosilicon compounds. However, the stability and controllability of the sol system are relatively poor, making it difficult to achieve large-scale processing of complex structural parts and components. It also has the drawback of a narrow range of application for the preparation process, that is, the process can only obtain SiO2 coatings on specific substrate surfaces. However, the surface chemical activity of metal materials and the reaction mechanism in the micro-arc oxidation process are different. This difference leads to a relatively complex and unique SiO2 ceramic coating preparation process. Therefore, it is very difficult to prepare similar SiO2 ceramic coatings on different metal material surfaces under the same process conditions. Summary of the Invention

[0005] The purpose of this invention is to provide a method for preparing an oxide ceramic coating, which has a wide range of applications and good stability and controllability.

[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution:

[0007] This invention provides a method for preparing an oxide ceramic coating, comprising the following steps:

[0008] The main film-forming agent, film-forming promoter, auxiliary film-forming agent and water are mixed to obtain a micro-arc oxidation electrolyte;

[0009] Using the substrate as the anode and a stainless steel coil as the cathode, the anode is placed in the micro-arc oxidation electrolyte for micro-arc oxidation treatment to obtain the oxide ceramic coating.

[0010] Preferably, the main film-forming agent comprises, by weight parts, 0-80 parts of sodium silicate, 0-80 parts of potassium silicate, 0-80 parts of lithium silicate, 0-120 parts of sodium silicate and 0-120 parts of potassium silicate, and the amounts of sodium silicate, potassium silicate, lithium silicate, sodium silicate and potassium silicate are not all 0.

[0011] Preferably, the film-forming accelerator comprises, by weight, 0-15 parts urea, 0-20 parts diethylene glycolamine, 0-25 parts triethanolamine and 0-30 parts polyacrylamide, wherein the amounts of urea, diethylene glycolamine, triethanolamine and polyacrylamide are all 0.

[0012] Preferably, the auxiliary film-forming agent comprises 0-30 parts of ethylene glycol, 0-35 parts of glycerol, 0-40 parts of diethylene glycol, and 0-45 parts of sorbitol, based on parts by weight, and the amounts of ethylene glycol, glycerol, diethylene glycol, and sorbitol are all 0.

[0013] Preferably, the concentration of the main film-forming agent in the micro-arc oxidation electrolyte is 100-200 g / L.

[0014] Preferably, the concentration of the film-forming promoter in the micro-arc oxidation electrolyte is 25–60 g / L.

[0015] Preferably, the concentration of the auxiliary film-forming agent in the micro-arc oxidation electrolyte is 50-100 g / L.

[0016] Preferably, the matrix is ​​an aluminum alloy, magnesium alloy, titanium alloy, copper alloy, or iron alloy.

[0017] Preferably, the micro-arc oxidation process is carried out under cyclic cooling conditions.

[0018] Preferably, the bipolar pulse power supply used in the micro-arc oxidation treatment has a frequency of 100–2000 Hz, a duty cycle of 8–40%, a positive voltage of 420–540 V, a negative voltage of 0–150 V, and a current density of 7.5–20 A / dm³. 2 The processing time is 30 to 120 minutes.

[0019] This invention provides a method for preparing an oxide ceramic coating, comprising the following steps: mixing a main film-forming agent, a film-forming promoter, an auxiliary film-forming agent, and water to obtain a micro-arc oxidation electrolyte; using a substrate as the anode and a stainless steel coil as the cathode, placing the anode in the micro-arc oxidation electrolyte and performing micro-arc oxidation treatment to obtain the oxide ceramic coating. The preparation method of this invention is universal, meaning that ceramic coatings with similar compositions and properties can be obtained on different metal material surfaces through the same process, greatly solving the problems of process complexity and controllability in the application of micro-arc oxidation technology. This invention has a wide range of applications, suitable for the preparation of non-substrate oxide ceramic coatings on the surfaces of various types and grades of metal materials, and also applicable to the surfaces of various complex structural components. Attached Figure Description

[0020] Figure 1 The images show macroscopic optical images, microscopic structure diagrams, and coating composition diagrams of the oxide ceramic coating described in Example 1.

[0021] Figure 2 The images show macroscopic optical images, microscopic structure diagrams, and coating composition diagrams of the oxide ceramic coating described in Example 2.

[0022] Figure 3 The images show macroscopic optical images, microscopic structural diagrams, and coating composition diagrams of the oxide ceramic coating described in Example 3. Detailed Implementation

[0023] This invention provides a method for preparing an oxide ceramic coating, comprising the following steps:

[0024] The main film-forming agent, film-forming promoter, auxiliary film-forming agent and water are mixed to obtain a micro-arc oxidation electrolyte;

[0025] Using the substrate as the anode and a stainless steel coil as the cathode, the anode is placed in the micro-arc oxidation electrolyte for micro-arc oxidation treatment to obtain the oxide ceramic coating.

[0026] In this invention, unless otherwise specified, all raw materials used in the preparation are commercially available products well known to those skilled in the art.

[0027] This invention mixes a main film-forming agent, a film-forming promoter, an auxiliary film-forming agent, and water to obtain a micro-arc oxidation electrolyte.

[0028] In this invention, the main film-forming agent preferably comprises 0-80 parts sodium silicate, 0-80 parts potassium silicate, 0-80 parts lithium silicate, 0-120 parts sodium silicate, and 0-120 parts potassium silicate, and the amounts of sodium silicate, potassium silicate, lithium silicate, sodium silicate, and potassium silicate are not all 0 at the same time; more preferably, it comprises 5 parts sodium silicate, 20 parts potassium silicate, 5 parts lithium silicate, and 120 parts sodium silicate; or 80 parts sodium silicate and 20 parts potassium silicate; or 20 parts sodium silicate, 5 parts potassium silicate, 20 parts lithium silicate, 35 parts sodium silicate, and 120 parts potassium silicate; or 80 parts lithium silicate, 20 parts sodium silicate, and 20 parts potassium silicate; or 30 parts sodium silicate, 80 parts potassium silicate, 30 parts lithium silicate, and 30 parts sodium silicate.

[0029] In this invention, the film-forming accelerator preferably comprises 0-15 parts urea, 0-20 parts diethylene glycolamine, 0-25 parts triethanolamine, and 0-30 parts polyacrylamide by weight, wherein the amounts of urea, diethylene glycolamine, triethanolamine, and polyacrylamide are not all 0; more preferably, it comprises 5 parts urea, 20 parts diethylene glycolamine, 10 parts triethylamine, and 5 parts polyacrylamide; or 15 parts urea, 10 parts diethylene glycolamine, 25 parts triethanolamine, and 10 parts polyacrylamide; or 10 parts urea, 5 parts diethylene glycolamine, and 10 parts triethanolamine; or 10 parts urea, 10 parts triethanolamine, and 30 parts polyacrylamide; or 10 parts diethylene glycolamine, 10 parts triethanolamine, and 10 parts polyacrylamide.

[0030] In this invention, the auxiliary film-forming agent preferably comprises 0-30 parts of ethylene glycol, 0-35 parts of glycerol, 0-40 parts of diethylene glycol, and 0-45 parts of sorbitol, based on parts by weight, wherein the amounts of ethylene glycol, glycerol, diethylene glycol, and sorbitol are not all 0; more preferably, it comprises 5 parts of ethylene glycol, 20 parts of glycerol, 40 parts of diethylene glycol, and 15 parts of sorbitol; or 35 parts of glycerol, 10 parts of diethylene glycol, and 5 parts of sorbitol; or 30 parts of ethylene glycol, 15 parts of glycerol, 10 parts of diethylene glycol, and 45 parts of sorbitol; or 15 parts of ethylene glycol, 20 parts of glycerol, 10 parts of diethylene glycol, and 15 parts of sorbitol; or 15 parts of ethylene glycol, 20 parts of glycerol, 25 parts of diethylene glycol, and 15 parts of sorbitol.

[0031] In this invention, the water is preferably deionized water.

[0032] In this invention, the mixing is preferably carried out under stirring conditions. This invention does not impose any special limitations on the stirring process, and any process well known to those skilled in the art can be used.

[0033] In this invention, the concentration of the main film-forming agent in the micro-arc oxidation electrolyte is preferably 100-200 g / L, more preferably 120-180 g / L, and most preferably 140-160 g / L; the concentration of the film-forming promoter in the micro-arc oxidation electrolyte is preferably 25-60 g / L, more preferably 30-50 g / L, and most preferably 35-45 g / L; and the concentration of the auxiliary film-forming agent in the micro-arc oxidation electrolyte is preferably 50-100 g / L, more preferably 60-90 g / L, and most preferably 79-80 g / L.

[0034] In this invention, controlling the type and amount of the main film-forming agent within the above-mentioned range affects the composition of the oxide film; controlling the type and amount of the film-forming promoter within the above-mentioned range affects the growth rate of the oxide film; and controlling the type and amount of the auxiliary film-forming agent within the above-mentioned range affects the microstructure of the oxide film.

[0035] After obtaining the micro-arc oxidation electrolyte, the present invention uses the substrate as the anode and the stainless steel coil as the cathode, places the anode in the micro-arc oxidation electrolyte, and performs micro-arc oxidation treatment to obtain the oxide ceramic coating.

[0036] Before placing the anode in the micro-arc oxidation electrolyte, the present invention preferably pre-treats the substrate, the pre-treatment preferably including polishing, cleaning and drying in sequence; the polishing is done with water-resistant sandpaper; the present invention does not have any special limitations on the polishing, cleaning and drying process, and any process known to those skilled in the art can be used.

[0037] In this invention, the matrix is ​​preferably an aluminum alloy, magnesium alloy, titanium alloy, copper alloy, or iron alloy. This invention does not impose any special limitations on the specific composition of the aluminum alloy, magnesium alloy, titanium alloy, copper alloy, and iron alloy; compositions well known to those skilled in the art can be used. In an embodiment of this invention, the aluminum alloy is specifically designated as 7A04, and by mass percentage, it comprises 1.4wt%–2.0wt% Cu, 1.8wt%–2.8wt% Mg, 0–0.5wt% Fe, 0–0.5wt% Si, 0.2wt%–0.6wt% Mn, 5.0wt%–7.0wt% Zn, 0.1wt%–0.2wt% Cr, 0–0.1wt% Ti, and the balance Al. The magnesium alloy is specifically designated ZK61M, and by weight percentage comprises 5.0wt%–6.0wt% Zn, 0.3wt%–0.9wt% Zr, 0–0.1wt% Mn, 0–0.05wt% Si, 0–0.05wt% Cu, 0–0.05wt% Fe, 0–0.01wt% Be, 0–0.005wt% Ni, and the balance Mg. The titanium alloy is specifically designated TC4, and by weight percentage comprises 0.3wt% Fe, 0.1wt% C, 0.05wt% N, 0.015wt% H, 0.2wt% O, 5.5wt%–6.8wt% Al, 3.5%–4.5wt% V, and the balance Ti. The copper alloy is specifically designated as H62, and by weight percentage comprises 60.5–63.5 wt% Cu, 0–0.15 wt% Fe, 0–0.08 wt% Pb, 0–0.005 wt% Sb, 0–0.002 wt% Bi, 0–0.001 wt% P, and the balance Zn. The ferroalloy is specifically designated as Q235, and by weight percentage comprises 0–0.17 wt% C, 0–1.4 wt% Mn, 0–0.35 wt% Si, 0–0.035 wt% S, 0–0.04 wt% P, and the balance Fe.

[0038] According to the embodiments, the solar absorptivity (α) of the oxide ceramic coating prepared on the surface of an aluminum alloy using the preparation method described in this invention is... s The α value ranged from 0.27 to 0.29, and the infrared emissivity (ε) ranged from 0.91 to 0.96; the α value of the oxide ceramic coating prepared on the magnesium alloy surface was... s The α value is 0.33–0.35, and the ε value is 0.87–0.90; the α value of the oxide ceramic coating prepared on the titanium alloy surface is... s The α value is 0.39–0.45, and the ε value is 0.92–0.94; the α value of the oxide ceramic coating prepared on the copper alloy surface is... s The α value is 0.40–0.48, and the ε value is 0.9–0.92; the α value of the oxide ceramic coating prepared on the surface of the ferroalloy is...s The value ranges from 0.41 to 0.50, and the ε value ranges from 0.89 to 0.91.

[0039] In this invention, the micro-arc oxidation treatment is preferably carried out under conditions of circulating cooling and stirring, and the circulating cooling conditions are preferably provided by a cooling water circulation system. This invention does not impose any special limitations on the stirring process; any process well-known to those skilled in the art can be used.

[0040] In this invention, the frequency of the bipolar pulse power supply used in the micro-arc oxidation treatment is preferably 100–2000 Hz, more preferably 500–1500 Hz, and most preferably 800–1200 Hz; the duty cycle is preferably 8–40%, more preferably 10–30%, and most preferably 15–25%; the positive voltage is preferably 420–540 V, more preferably 450–500 V, and most preferably 460–480 V; the negative voltage is preferably 0–150 V, more preferably 30–120 V, and most preferably 50–100 V; and the current density is preferably 7.5–20 A / dm³. 2 More preferably 10–19 A / dm 2 The optimal value is 13-16 A / dm. 2 The processing time is preferably 30 to 120 minutes, more preferably 50 to 100 minutes, and most preferably 60 to 80 minutes.

[0041] In this invention, the reactions and changes that occur during the micro-arc oxidation process are a cycle of adsorption-deposition-sintering of silicate ions in the electrolyte.

[0042] After the micro-arc oxidation treatment is completed, the present invention preferably includes sequential cleaning and drying; the cleaning is preferably performed by rinsing with deionized water; the present invention does not have any special limitations on the rinsing and drying process, and any process known to those skilled in the art can be used.

[0043] The oxide ceramic coating prepared on the substrate surface using the method described in this invention exhibits a low solar absorptivity and a high infrared emissivity. Its solar absorptivity (α...) s The solar absorptivity (ε) is adjustable within the range of 0.27 to 0.50, and the infrared emissivity (ε) is adjustable within the range of 0.87 to 0.96. The solar absorptivity of the oxide ceramic coating was tested according to GJB 2502.2-2006 "Test Methods for Thermal Control Coatings of Spacecraft - Part 2: Solar Absorption Ratio Test", and the infrared emissivity of the oxide ceramic coating was tested according to GJB 2502.2-2006 "Test Methods for Thermal Control Coatings of Spacecraft - Part 3: Emissivity Test". The results show that the oxide ceramic coating can be widely used as a thermal control coating on the surface of structural components such as metal materials in aerospace products and a thermal radiation coating on the surface of electronic components.

[0044] The following detailed description of the preparation method of the oxide ceramic coating provided by the present invention, in conjunction with the embodiments, should not be construed as limiting the scope of protection of the present invention.

[0045] Example 1

[0046] After polishing the aluminum alloy (model 7A04) with water-resistant sandpaper, it was rinsed with tap water, cleaned with deionized water and dried to obtain the pretreated aluminum alloy substrate.

[0047] Add the main film-forming agent (sodium silicate, potassium silicate, lithium silicate and sodium silicate in a mass ratio of 5:20:5:120), the film-forming accelerator (urea, diethylene glycolamine, triethylamine and polyacrylamide in a mass ratio of 5:20:10:5), and the auxiliary film-forming agent (ethylene glycol, glycerol, diethylene glycol and sorbitol in a mass ratio of 5:20:40:15) to deionized water and stir thoroughly until dissolved to obtain a micro-arc oxidation electrolyte (the concentration of the main film-forming agent is 150 g / L, the concentration of the film-forming accelerator is 40 g / L, and the concentration of the auxiliary film-forming agent is 80 g / L).

[0048] Using the pretreated aluminum alloy substrate as the anode and a stainless steel coil as the cathode, the anode is placed in the micro-arc oxidation electrolyte. The cooling water circulation system is turned on, and a bipolar pulse power supply in constant voltage mode is used, with a power frequency of 1200Hz, a duty cycle of 15%, a positive voltage of 500V, a negative voltage of 100V, and a current density of 12A / dm³. 2 Under the conditions of stirring, the pretreated aluminum alloy is subjected to micro-arc oxidation for 60 minutes until the ceramic coating reaches a thickness of 90 micrometers. After the micro-arc oxidation is completed, the aluminum alloy is removed, and the mixture is rinsed with tap water and deionized water in sequence and then dried to obtain an oxide ceramic coating with α... s The value is 0.28, and ε is 0.95.

[0049] Example 2

[0050] An oxide ceramic coating was prepared according to Example 1, the difference being that the aluminum alloy was replaced with a magnesium alloy (model ZK61M), and its α s The value is 0.34, and ε is 0.90.

[0051] Example 3

[0052] An oxide ceramic coating was prepared according to Example 1, the difference being that the aluminum alloy was replaced with a titanium alloy (model TC4), whose α s The value is 0.40, and ε is 0.93.

[0053] Example 4

[0054] An oxide ceramic coating was prepared according to Example 1, the difference being that the aluminum alloy was replaced with a copper alloy (model H62), and its α s The value is 0.41, and ε is 0.91.

[0055] Example 5

[0056] An oxide ceramic coating was prepared according to Example 1, the difference being that the aluminum alloy was replaced with an iron alloy (type Q235), and its α s The value is 0.42, and ε is 0.9.

[0057] Figure 1 The images shown are macroscopic optical images, microscopic structure diagrams, and coating composition diagrams of the oxide ceramic coating described in Example 1. Figure 2 The images shown are macroscopic optical images, microscopic structure diagrams, and coating composition diagrams of the oxide ceramic coating described in Example 2. Figure 3 The images show macroscopic optical images, microstructure diagrams, and coating composition diagrams of the oxide ceramic coating described in Example 3; [The remaining text appears to be a fragmented and incomplete description of the image, possibly related to an example or diagram.] Figures 1-3 As shown, the oxide ceramic coatings prepared under the same preparation conditions have basically the same apparent color and good surface uniformity. Due to the influence of the alloy matrix material, the microstructure of the oxide ceramic coatings is slightly different, but the composition of the oxide ceramic coatings is mainly silicon dioxide.

[0058] Examples 6-10

[0059] After polishing the alloy with water-resistant sandpaper, it was rinsed with tap water, cleaned with deionized water and dried to obtain the pretreated alloy matrix (among which, Example 6 is an aluminum alloy of type 7A04, Example 7 is a magnesium alloy of type ZK61M, Example 8 is a titanium alloy of type TC4, Example 9 is a copper alloy of type H62, and Example 10 is an iron alloy of type Q235).

[0060] Add the main film-forming agent (sodium silicate and potassium silicate in a mass ratio of 80:20), the film-forming accelerator (urea, diethylene glycolamine, triethanolamine and polyacrylamide in a mass ratio of 15:10:25:10), and the auxiliary film-forming agent (glycerol, diethylene glycol and sorbitol in a mass ratio of 35:10:5) to deionized water and stir thoroughly until dissolved to obtain a micro-arc oxidation electrolyte (the concentration of the main film-forming agent is 100 g / L, the concentration of the film-forming accelerator is 60 g / L, and the concentration of the auxiliary film-forming agent is 50 g / L).

[0061] Using the pretreated aluminum alloy substrate as the anode and a stainless steel coil as the cathode, the anode is placed in the micro-arc oxidation electrolyte. The cooling water circulation system is turned on, and a bipolar pulse power supply in constant voltage mode is used, with a power frequency of 100Hz, a duty cycle of 40%, a positive voltage of 540V, a negative voltage of 0V, and a current density of 20A / dm³. 2 Under the conditions of stirring, the pretreated aluminum alloy is subjected to micro-arc oxidation treatment for 120 minutes until the ceramic coating reaches a thickness of 85 micrometers. After the micro-arc oxidation treatment is completed, the aluminum alloy is removed and then rinsed with tap water and deionized water and dried to obtain the oxide ceramic coating.

[0062] Examples 6-10 show that the oxide ceramic coatings prepared under the same conditions have basically the same apparent color and good surface uniformity. The α-coatings of the oxide ceramic coatings on their surfaces exhibit good variability. s The values ​​were 0.28, 0.34, 0.42, 0.43 and 0.45 respectively; the values ​​of ε were 0.93, 0.89, 0.93, 0.91 and 0.90 respectively.

[0063] Examples 11-15

[0064] After polishing the alloy with water-resistant sandpaper, it was rinsed with tap water, cleaned with deionized water and dried to obtain the pretreated alloy matrix (among which, Example 11 is an aluminum alloy of type 7A04, Example 12 is a magnesium alloy of type ZK61M, Example 13 is a titanium alloy of type TC4, Example 14 is a copper alloy of type H62, and Example 15 is an iron alloy of type Q235).

[0065] Add the main film-forming agent (sodium silicate, potassium silicate, lithium silicate, sodium silicate and potassium silicate in a mass ratio of 20:5:20:35:120), the film-forming accelerator (urea, diethylene glycol and triethanolamine in a mass ratio of 10:5:10), and the auxiliary film-forming agent (ethylene glycol, glycerol, diethylene glycol and sorbitol in a mass ratio of 30:15:10:45) to deionized water and stir thoroughly until dissolved to obtain a micro-arc oxidation electrolyte (the concentration of the main film-forming agent is 200 g / L, the concentration of the film-forming accelerator is 25 g / L, and the concentration of the auxiliary film-forming agent is 100 g / L).

[0066] Using the pretreated aluminum alloy substrate as the anode and a stainless steel coil as the cathode, the anode is placed in the micro-arc oxidation electrolyte. The cooling water circulation system is turned on, and a bipolar pulse power supply in constant voltage mode is used, with a power frequency of 2000Hz, a duty cycle of 8%, a positive voltage of 420V, a negative voltage of 150V, and a current density of 7.5A / dm³. 2Under the conditions of stirring, the pretreated aluminum alloy is subjected to micro-arc oxidation treatment for 30 minutes until the ceramic coating reaches a thickness of 100 micrometers. After the micro-arc oxidation treatment is completed, the aluminum alloy is removed and then rinsed with tap water and deionized water and dried to obtain the oxide ceramic coating.

[0067] Examples 11-15 show that the oxide ceramic coatings prepared under the same conditions have basically the same apparent color and good surface uniformity. The α-coatings of the oxide ceramic coatings on their surfaces exhibit good variability. s The values ​​were 0.27, 0.33, 0.39, 0.40 and 0.41, respectively; and the values ​​of ε were 0.96, 0.9, 0.94, 0.92 and 0.91, respectively.

[0068] Examples 16-20

[0069] After polishing the alloy with water-resistant sandpaper, it was rinsed with tap water, cleaned with deionized water and dried to obtain the pretreated alloy matrix (among which, Example 16 is an aluminum alloy of type 7A04, Example 17 is a magnesium alloy of type ZK61M, Example 18 is a titanium alloy of type TC4, Example 19 is a copper alloy of type H62, and Example 20 is an iron alloy of type Q235).

[0070] Add the main film-forming agent (lithium silicate, sodium silicate, and potassium silicate in a mass ratio of 80:20:20), the film-forming accelerator (urea, triethanolamine, and polyacrylamide in a mass ratio of 10:10:30), and the auxiliary film-forming agent (ethylene glycol, glycerol, diethylene glycol, and sorbitol in a mass ratio of 15:20:10:15) to deionized water and stir thoroughly until dissolved to obtain a micro-arc oxidation electrolyte (the concentration of the main film-forming agent is 120 g / L, the concentration of the film-forming accelerator is 50 g / L, and the concentration of the auxiliary film-forming agent is 60 g / L).

[0071] Using the pretreated aluminum alloy substrate as the anode and a stainless steel coil as the cathode, the anode is placed in the micro-arc oxidation electrolyte. The cooling water circulation system is turned on, and a bipolar pulse power supply in constant voltage mode is used, with a power frequency of 800Hz, a duty cycle of 25%, a positive voltage of 480V, a negative voltage of 80V, and a current density of 15A / dm³. 2 Under the conditions of stirring, the pretreated aluminum alloy is subjected to micro-arc oxidation treatment for 90 minutes until the ceramic coating reaches a thickness of 75 micrometers. After the micro-arc oxidation treatment is completed, the aluminum alloy is removed and then rinsed with tap water and deionized water and dried to obtain the oxide ceramic coating.

[0072] Examples 16-20 show oxide ceramic coatings prepared under the same conditions with basically consistent apparent colors and good surface uniformity. The α-coatings of these oxide ceramic coatings exhibit good surface uniformity. s The values ​​were 0.29, 0.34, 0.44, 0.46 and 0.48 respectively; the values ​​of ε were 0.94, 0.88, 0.91, 0.9 and 0.9 respectively.

[0073] Examples 21-25

[0074] After polishing the alloy with water-resistant sandpaper, it was rinsed with tap water, cleaned with deionized water and dried to obtain the pretreated alloy matrix (among which, Example 21 is an aluminum alloy of type 7A04, Example 22 is a magnesium alloy of type ZK61M, Example 23 is a titanium alloy of type TC4, Example 24 is a copper alloy of type H62, and Example 25 is an iron alloy of type Q235).

[0075] Add the main film-forming agent (sodium silicate, potassium silicate, lithium silicate, and sodium silicate in a mass ratio of 30:80:30:30), the film-forming promoter (diethylene glycolamine, triethanolamine, and polyacrylamide in a mass ratio of 10:10:10), and the auxiliary film-forming agent (ethylene glycol, glycerol, diethylene glycol, and sorbitol in a mass ratio of 15:20:25:15) to deionized water and stir thoroughly until dissolved to obtain a micro-arc oxidation electrolyte (the concentration of the main film-forming agent is 120 g / L, the concentration of the film-forming promoter is 50 g / L, and the concentration of the auxiliary film-forming agent is 60 g / L).

[0076] Using the pretreated aluminum alloy substrate as the anode and a stainless steel coil as the cathode, the anode is placed in the micro-arc oxidation electrolyte. The cooling water circulation system is turned on, and a bipolar pulse power supply in constant voltage mode is used, with a power frequency of 300Hz, a duty cycle of 12%, a positive voltage of 450V, a negative voltage of 120V, and a current density of 10A / dm³. 2 Under the conditions of stirring, the pretreated aluminum alloy is subjected to micro-arc oxidation treatment for 45 minutes until the ceramic coating reaches a thickness of 65 micrometers. After the micro-arc oxidation treatment is completed, the aluminum alloy is removed and then rinsed with tap water and deionized water and dried to obtain the oxide ceramic coating.

[0077] Examples 21-25 show that the oxide ceramic coatings prepared under the same conditions have basically the same apparent color and good surface uniformity. The α-coatings of the oxide ceramic coatings on their surfaces exhibit good variability. s The values ​​were 0.29, 0.35, 0.45, 0.48 and 0.5 respectively; the values ​​of ε were 0.91, 0.87, 0.92, 0.9 and 0.89 respectively.

[0078] The above description is only a preferred embodiment of the present invention. It should be noted that those skilled in the art can make several improvements and modifications without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing an oxide ceramic coating, characterized in that, Includes the following steps: The main film-forming agent, film-forming promoter, auxiliary film-forming agent and water are mixed to obtain a micro-arc oxidation electrolyte; Using a substrate as the anode and a stainless steel coil as the cathode, the anode is placed in the micro-arc oxidation electrolyte and subjected to micro-arc oxidation treatment to obtain the oxide ceramic coating; the oxide ceramic coating is mainly composed of silicon dioxide. The main film-forming agent is sodium silicate, potassium silicate, lithium silicate, and sodium silicate in a mass ratio of 5:20:5:120; the film-forming accelerator is urea, diethylene glycolamine, triethylamine, and polyacrylamide in a mass ratio of 5:20:10:5; the auxiliary film-forming agent is ethylene glycol, glycerol, diethylene glycol, and sorbitol in a mass ratio of 5:20:40:15; the concentration of the main film-forming agent in the micro-arc oxidation electrolyte is 150 g / L, the concentration of the film-forming accelerator is 40 g / L, and the concentration of the auxiliary film-forming agent is 80 g / L. Alternatively, the primary film-forming agent may be sodium silicate and potassium silicate in a mass ratio of 80:20; the film-forming accelerator may be urea, diethylene glycolamine, triethanolamine, and polyacrylamide in a mass ratio of 15:10:25:10; the auxiliary film-forming agent may be glycerol, diethylene glycol, and sorbitol in a mass ratio of 35:10:5; the concentration of the primary film-forming agent in the micro-arc oxidation electrolyte may be 100 g / L, the concentration of the film-forming accelerator may be 60 g / L, and the concentration of the auxiliary film-forming agent may be 50 g / L. Alternatively, the main film-forming agent may be sodium silicate, potassium silicate, lithium silicate, sodium silicate glass, and potassium silicate glass in a mass ratio of 20:5:20:35:120; the film-forming accelerator may be urea, diethylene glycol, and triethanolamine in a mass ratio of 10:5:10; the auxiliary film-forming agent may be ethylene glycol, glycerol, diethylene glycol, and sorbitol in a mass ratio of 30:15:10:45; the concentration of the main film-forming agent in the micro-arc oxidation electrolyte may be 200 g / L, the concentration of the film-forming accelerator may be 25 g / L, and the concentration of the auxiliary film-forming agent may be 100 g / L. Alternatively, the main film-forming agent may be lithium silicate, sodium silicate, and potassium silicate in a mass ratio of 80:20:20; the film-forming accelerator may be urea, triethanolamine, and polyacrylamide in a mass ratio of 10:10:30; the auxiliary film-forming agent may be ethylene glycol, glycerol, diethylene glycol, and sorbitol in a mass ratio of 15:20:10:15; and the concentration of the main film-forming agent in the micro-arc oxidation electrolyte may be 120 g / L, the concentration of the film-forming accelerator may be 50 g / L, and the concentration of the auxiliary film-forming agent may be 60 g / L. Alternatively, the main film-forming agent may be sodium silicate, potassium silicate, lithium silicate, and sodium silicate in a mass ratio of 30:80:30:30; the film-forming accelerator may be diethylene glycolamine, triethanolamine, and polyacrylamide in a mass ratio of 10:10:10; the auxiliary film-forming agent may be ethylene glycol, glycerol, diethylene glycol, and sorbitol in a mass ratio of 15:20:25:15; the concentration of the main film-forming agent in the micro-arc oxidation electrolyte may be 120 g / L, the concentration of the film-forming accelerator may be 50 g / L, and the concentration of the auxiliary film-forming agent may be 60 g / L. The substrate is made of aluminum alloy, magnesium alloy, titanium alloy, copper alloy, or iron alloy.

2. The preparation method according to claim 1, characterized in that, The micro-arc oxidation process is carried out under cyclic cooling conditions.

3. The preparation method according to claim 2, characterized in that, The micro-arc oxidation process uses a bipolar pulse power supply with a frequency of 100~2000Hz, a duty cycle of 8~40%, a positive voltage of 420~540V, a negative voltage of 0~150V, and a current density of 7.5~20A / dm³. 2 The processing time is 30~120 minutes.

Citation Information

Patent Citations

  • Preparation method of titanium alloy surface coating with low solar absorptivity and high emissivity

    CN103194780A

  • A method for preparing a conductive thermal control coating with low solar absorptivity and high emissivity on an aluminum alloy surface

    CN108950549B

  • Method for preparing nano ceramic coating by using ceramic particle chemical self-sintering micro-arc oxidation technology

    CN110983408A

  • Preparation method of magnesium alloy self-supporting micro-arc oxidation film layer

    CN113564662A

  • An amorphous silicon dioxide coating prepared based on micro-arc oxidation and a preparation method and application thereof

    CN116497419B